Recent Development of Biomass Conversion using Ionic Liquid-based Processes - Megawati Zunita; Risha Diah Rhamadhani (ASEAN Journal of Chemical Engineering, 2021)
The amount of biomass products generated globally increases year after year. Nature produces lignocellulose, which is largely constituted of three components in the following order: cellulose (34–50%), hemicellulose (15–35%), and lignin (5–30%). A promising conversion method known as biomass conversion employs a liquid media-based process to address the issue of an abundance of biomass as waste. Converting biomass with ionic liquid (IL) can address not only environmental issues caused by the abundance of biomass waste but also generate new energy sources or new products with economical selling value. IL can be employed as a green catalyst, solvent, or electrolyte, as well as in a number of conversion processes. In general, 1-alkyl-3-methyl-imidazolium-based cations are the most commonly used IL types for biomass conversion. The conversion conditions are relatively mild, consisting of a low temperature of around 95-220 °C, 1 atm, for 10–240 minutes. This paper review is expected to be a significant reference in the future for the development of other biomass conversion processes.